2012
DOI: 10.1002/ase.1332
|View full text |Cite
|
Sign up to set email alerts
|

Talking about death: Implementing peer discussion as a coping mechanism to overcome fears about dissection, death, and dying

Abstract: Many studies have reported on the perceptions of medical students toward dissection. It is important to understand the feelings and symptoms experienced during dissection so that they can be adequately handled. Prior to dissection, first year students are given lectures on aspects of dissection, death and dying, and death rituals in various cultures. Two separate questionnaires, one given during the first week of dissection and another given one month into the program were then completed anonymously by dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 73 publications
(17 reference statements)
9
42
1
2
Order By: Relevance
“…Lecturers observed that it stimulated discussion on the cadaver pathology within and between dissection groups. A previous study conducted at our institution demonstrated that one of the main benefits which students hope to gain from dissection was an improvement of their theoretical morphological knowledge (Kotzé and Mole, ). The integration of pathology into dissection further aids in this outcome by emphasizing the clinical importance of anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lecturers observed that it stimulated discussion on the cadaver pathology within and between dissection groups. A previous study conducted at our institution demonstrated that one of the main benefits which students hope to gain from dissection was an improvement of their theoretical morphological knowledge (Kotzé and Mole, ). The integration of pathology into dissection further aids in this outcome by emphasizing the clinical importance of anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relevance of cadaver dissection in the training of medical students often debate the advantages and disadvantages thereof from the point of view of both students and lecturers (Ellis, ; Aziz et al, ; Granger, ; McLachlan and Patten, ; Gregory et al, ; Kotzé and Mole, ). It has however been argued that many of the “advantages” of cadaver dissection may be obtained by other pedagogical modalities such as prosections, plastinated specimens, living anatomy, medical imaging, and traditional didactic lectures and textbooks (McLachlan and Regan De Bere, ; McLachlan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Students may occasionally experience apprehension, interest or even a morbid curiosity when physically faced with death. Researchers have described a "rite of passage," "socializing with death" and sometimes even a process of dehumanization in relation to dissection (Dickinson et al, 1997;Plaisant et al, 2011;Kotzé and Mole, 2013;Sandor et al, 2015;Dosani and Neuberger, 2016). It is one of the first professional contacts with death (Abu-Hijelh et al, 1997;Tschernig et al, 2000;Boeckers and Boeckers, 2016;Goodwin et al, 2016), but the experience can be satisfying, with 76% of students stating that they believed it could not be replaced with any alternative material or model (Mompeó Corredera, 2014;Sandor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, religion and spirituality did not appear to have a major affect on our students' responses with many who did not identify as having religious or spiritual belongings still believing in the soul. Others have found that despite having a low proportion of “religious” students, 35% of their class believed in the concept of heaven and hell and 30% believed in an eternal afterlife, similar to the concept of the soul (Kotzé and Mole, ). Some of their students (19%) also viewed the body as merely a shell to house the soul, not required for transition to an afterlife (Kotzé and Mole, ).…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that despite having a low proportion of "religious" students, 35% of their class believed in the concept of heaven and hell and 30% believed in an eternal afterlife, similar to the concept of the soul (Kotz e and Mole, 2013). Some of their students (19%) also viewed the body as merely a shell to house the soul, not required for transition to an afterlife (Kotz e and Mole, 2013).…”
Section: Discussionmentioning
confidence: 99%